Pengaruh Formulasi Penambahan Biochar terhadap Produksi Tanaman Tembakau Varietas K326 Cross Creek Seed USA. di Lahan Kering Kabupaten Bojonegoro - Pahlevi, Reza Widhi; Susilo, Buana; Dalimartha, Lengga Nurullah; Wiguna, Eko Chandra; Isdiantoni, Isdiantoni; Koentjoro, Maharani Pertiwi; Prasetiyo, Endry Nugroho (Universitas Sebelas Maret, 2017)
Tobacco plant has high value and strongly sensitive to physical and chemical conditions of soil condition. One alternative to increase tobacco production is modify the soil using biochar accompanied with other organic materials such as fertilizer. This research aimed to determine the best formulation on addition of biochar to the yield of tobacco (Nicotiana tabacum) plants var. K326. The study was conducted in Balen Subdistrict, Bojonegoro District, East Java, Indonesia with Randomized Block Design consisting of 5 treatments. Prior aplication the biochar was formulated with compost, OCF (Organic Compound Fertilizer), and agricultural waste. The formulation is intended to allow biochar having adequate nutrient content to increase tobacco yield. Biochar treatment formulated with OCF gave 45,8 % higher of tobacco yield than the control by 1,084 ton ha-1 and 0,497 ton ha-1 respectively.